Web-based viewing of picture archiving and communications systems images -- part II: the effect of compression on speed of transmission...Proccedings of the 16th Symposium for Computer Applications in Radiology. 'PACS: Performance Improvement in Radiology.' Houston TX, May 6-9, 1999 - Bennett WF; Spigos DG; Tzalonikou MT; Terrell JE; Augustyn MA (Journal of Digital Imaging)
Now that picture archiving and communications systems (PACS) has matured, our challenge is to make the images available to the referring physician and, in a teaching institution, to make these images available for conferences and rounding. One solution is the distribution of the images using web-based technology. We investigated a web-based add-on to our PACS to determine the characteristics of the personal computer that will make this technology useful and affordable. We found that images can be viewed easily through a web-based system. We found that the optimal system to view these images at a reasonable speed and a reasonable cost is on with a medium-range processor (200 to 300 MHz) and a large amount of inexpensive RAM, at least 64 Mb. Copyright (c) 1999 by W.B. Saunders Company